PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DAN LOYALITAS PELANGGAN PADA PRODUK KECANTIKAN MEREK MAKE OVER DI KOTA PEKANBARU - Jayanti, Elda; Samsir, Samsir; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research is done on Beauty Products Brand Make Over in Pekanbaru City. With the aim to know and analyze the influence of product quality and brand image to customer satisfaction and customer loyalty On beauty products make over brand In Pekanbaru City. Where in this study population is women who have age 20 to 49 years who is domiciled in Pekanbaru City Riau Province. The sample used in this research is 104 customer and data processing using path analysis method. Based on the results of the test if the data by using the path analysis can be taken several conclusions are: there is a significant influence between product quality variables on customer satisfaction, there is a significant influence between brand image variable to customer satisfaction, there is a significant influence between product quality variables on customer loyalty , there is significant influence between variable of brand image to customer satisfaction, there is significant influence between customer satisfaction variable to customer loyalty, there is significant influence between product quality variable to customer loyalty through customer satisfaction, and there is no significant influence between variable of brand image to customer loyalty through customer satisfaction.Keyword: Product Quality, Brand Image, Satisfaction and Loyalty